Deaf and Hard of Hearing Students with Disabilities: An Evolving Landscape - Sandy K. Bowen; Kristi M. Probst (MDPI AG, 2023)
The population of students who are d/Deaf or hard of hearing (d/Dhh) with a disability have unique educational needs. Various terms have been used to describe this population, including "deaf plus", "deaf with additional disabilities", and most recently, "deaf with disabilities (DWD)". Currently, there is no agreement on the percentage of DWD students in PreK-21 settings but is considered to comprise at least 40-50%. An individual who is DWD has a hearing loss and one or more disabilities, including (but not limited to) visual impairment or blindness, autism spectrum disorder, intellectual or developmental disabilities, specific learning disabilities, health impairments, etc. The critical consideration is that the interaction between hearing loss and the disability(ies) is not simply additive but rather multiplicative, impacting communication, cognition, social development, and behavior. Furthermore, the presence of hearing loss may decrease accurate identification of other disabilities and vice versa. Although the incidence of students who are DWD is quite high, there is inadequate research as these students are often excluded from studies focused on children who are d/Dhh. This article explores what we currently know about DWD students, and the knowledge and skills needed by teachers in the 21st century to meet the needs of these students and their families.